Functional Behavioral Assessment: The Link between Problem Behavior and Effective Intervention in Schools - Jeffrey A. Miller; Michael Tansy; Tammy L. Hughes (Arizona State University, 2015)
An important current issue in education is the mandate in the 1997 reauthorization of the Individuals with Disabilities Education Act (Individuals with Disabilities Education Act Amendments of 1997) that schools must conduct a functional behavioral assessment when a student's behavior disrupts the educational environment. This article reviews the literature on functional analysis and how it relates to the legal mandate for functional behavioral assessment in schools. Functional behavioral assessment is considered an important and frequently missing link between topographical descriptions of behavior and treatment planning. Problems with existing functional behavioral assessment methodologies include the complexity of data synthesis and treatment selection. Also, existing efforts to define functional behavioral assessment have not included sufficiently diverse theoretical models for the causes of behavior or for treatment. In contrast, we provide a definition of functional behavioral assessment that includes proximal, distal, physiological, and intrapsychic causes of problem behavior. Based on this definition, a multimodal, team problem-solving approach to conducting functional behavioral assessments and developing behavior intervention plans in schools is proposed. The proposed approach distributes complex decision making across team members, includes multiple theoretical perspectives, can be readily adopted by existing child study teams, and is in compliance with the 1997 reauthorization of the Individuals with Disabilities Education Act.